Biostimulant action of a plant-derived protein hydrolysate produced through enzymatic hydrolysis - Colla, Giuseppe; Rouphael, Youssef; Canaguier, Renaud; Svecova, Eva; Cardarelli, Mariateresa (Frontiers in Plant Science, 2014)
The aim of this study was to evaluate the biostimulant action (hormone like activity, nitrogen uptake, and growth stimulation) of a plant-derived protein hydrolysate by means of two laboratory bioassays: a corn (Zea mays L.) coleoptile elongation rate test (experiment 1), a rooting test on tomato cuttings (experiment 2); and two greenhouse experiments: a dwarf pea (Pisum sativum L.) growth test (experiment 3), and a tomato (Solanum lycopersicum L.) nitrogen uptake trial (experiment 4). Protein hydrolysate treatments of corn caused an increase in coleoptile elongation rate when compared to the control, in a dose-dependent fashion, with no significant differences between the four concentrations tested (0.375, 0.75, 1.5, and 3.0 ml/L), and inodole-3-acetic acid (IAA) treatment. The auxin-like effect of the protein hydrolysate on corn has been also observed in the rooting experiment of tomato cuttings. The shoot, root dry weight, root length, and root area were significantly higher by 21%, 35%, 24%, and 26%, respectively in tomato treated plants with the protein hydrolysate at 6 ml/L than untreated plants. In experiment 3, the application of the protein hydrolysate at all doses (0.375, 0.75, 1.5, and 3.0 ml/L) significantly increased the shoot length of the giberellin (GA)-deficient dwarf pea plants by an average value of 33% in comparison with the control treatment. Increasing the concentration of the protein hydrolysate from 0 to 10 ml/L increased the total dry biomass, SPAD index, and leaf nitrogen content by 20.5%, 15% and 21.5%, respectively. Thus the application of plant-derived protein hydrolysate containing amino acids and small peptides elicited a hormone-like activity, enhanced nitrogen uptake and consequently crop performances.